2023
DOI: 10.1186/s40942-023-00482-9
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Choroidal Vascular Biomarkers in Eyes with Rhegmatogenous Retinal Detachment-Related Giant Retinal Tears

Abstract: Purpose Choroidal vascularity index (CVI) and choriocapillaris flow area (CFA) are perfusion biomarkers relevant to retinal disease management. There is limited knowledge regarding these biomarkers in eyes that have been successfully treated for rhegmatogenous retinal detachment (RRD) due to giant retinal tears (GRTs). This study aimed to analyze the relationship between choroidal perfusion biomarkers and functional outcomes in surgically treated eyes with GRT-associated RRD and their fellow ey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Quiroz-Reyes et al have shown how critical CVI and CFA are used to evaluate perfusion in different pathologies, such as GRT-related RRD postoperative evaluation, and surgically resolved MTM eyes, which generally exhibit larger superficial postoperative FAZs, smaller CFAs, lower VDs, more structural macular defects, and thinner CSFTs [35,68]. Better functional, structural, and perfusion index outcomes were observed in highly myopic eyes that underwent early surgery.…”
Section: Literature Review and Discussionmentioning
confidence: 99%
“…Quiroz-Reyes et al have shown how critical CVI and CFA are used to evaluate perfusion in different pathologies, such as GRT-related RRD postoperative evaluation, and surgically resolved MTM eyes, which generally exhibit larger superficial postoperative FAZs, smaller CFAs, lower VDs, more structural macular defects, and thinner CSFTs [35,68]. Better functional, structural, and perfusion index outcomes were observed in highly myopic eyes that underwent early surgery.…”
Section: Literature Review and Discussionmentioning
confidence: 99%